2016
DOI: 10.1007/s11845-016-1473-z
|View full text |Cite
|
Sign up to set email alerts
|

Late effects of chemotherapeutic agents on renal function in childhood cancer survivors: a review of the literature

Abstract: As more childhood cancer survivors are reaching adulthood, a new niche of cancer research has emerged. Researchers are now investigating the late effects due to cytotoxic treatments. Renal function impairment is a potential late effect of treatment with nephrotoxic chemotherapeutic agents including ifosfamide, cisplatin, carboplatin and methotrexate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…It can lead to rickets and growth impairment and has been described as occurring in 5 to 7% of paediatric patients treated with ifosfamide. 2,6 Our patient presented with metabolic acidosis, hypophosphatemia, hypokalemia, hypouricemia, proteinuria and glycosuria. Further testing showed low tubular reabsorption of phosphorus and high fractional excretion of potassium and uric acid, thus confirming the diagnosis of Fanconi syndrome.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…It can lead to rickets and growth impairment and has been described as occurring in 5 to 7% of paediatric patients treated with ifosfamide. 2,6 Our patient presented with metabolic acidosis, hypophosphatemia, hypokalemia, hypouricemia, proteinuria and glycosuria. Further testing showed low tubular reabsorption of phosphorus and high fractional excretion of potassium and uric acid, thus confirming the diagnosis of Fanconi syndrome.…”
Section: Discussionmentioning
confidence: 95%
“…5 It has been described as a late effect of Ifosfamide in only 5 to 7% of patients treated. 2,6 In this case report the authors describe a case of Fanconi syndrome diagnosed 17 months after exposure to ifosfamide for Burkitt lymphoma treatment.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Childhood cancer patients face additional health risks due to exposure to radiation and chemotherapy during early life growth and development. Recent literature reviews reported the following late adverse effects childhood cancer: increased risk of subsequent primary malignancies, hypothyroidism, severe fatigue, hearing loss organ dysfunctions (ovarian, liver, lungs, heart, kidney and bladder), obesity as well as musculoskeletal, dental and psychosocial effects [15][16][17][18][19][20][21]. The Australian healthcare system consists of both public and private providers.…”
Section: Introductionmentioning
confidence: 99%